2023
DOI: 10.1089/can.2023.0128
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biological Activities of Cannflavins of the Cannabis Plant

Maged S. Abdel-Kader,
Mohamed M. Radwan,
Ahmed M. Metwaly
et al.

Abstract: Background: Throughout history, Cannabis has had a significant influence on human life as one of the earliest plants cultivated by humans. The plant was a source of fibers used by the oldest known civilizations. Cannabis was also used medicinally in China, India, and ancient Egypt. Delta-9-tetrahydrocannabinol (Δ 9 -THC), the main psychoactive compound in the plant was identified in 1964 followed by more than 125 cannabinoids. More than 30 flavonoids were isolated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Cannabis plants also have unique compounds, such as cannflavins, which are specific to the plant ( Figure 3 ) [ 57 ]. These compounds, including cannflavin A, cannflavin B, and cannflavin C, have been studied for their diverse biological activities, particularly their anti-inflammatory and anticancer effects [ 58 ]. In addition to their anti-inflammatory effects, cannflavins have also demonstrated anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis plants also have unique compounds, such as cannflavins, which are specific to the plant ( Figure 3 ) [ 57 ]. These compounds, including cannflavin A, cannflavin B, and cannflavin C, have been studied for their diverse biological activities, particularly their anti-inflammatory and anticancer effects [ 58 ]. In addition to their anti-inflammatory effects, cannflavins have also demonstrated anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…Although alcohol consumption concomitant with marijuana has been reported as a trigger of cannabis-related strokes [ 21 ], studies on the effects of simultaneous alcohol-marijuana administration on cerebral artery or arteriole diameter are scarce. Our recent studies in male and female rats focused on THC as a major psychoactive substance with one of the highest percentual presence in marijuana leaves [ 13 , 22 ]. The study by Slayden et al [ 13 ] demonstrated that the in vivo constriction of cerebral arteries by simultaneous alcohol and THC administration in each sex did not statistically differ from constriction produced by alcohol alone.…”
Section: Introductionmentioning
confidence: 99%